2013
DOI: 10.2169/internalmedicine.52.9088
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Viral Load in Cerebrospinal Fluid as a Diagnostic Marker of Central Nervous System Involvement of AIDS-related Lymphoma

Abstract: Objective AIDS-related lymphoma (ARL) often involves the central nervous system (CNS). Although the diagnostic value of Epstein-Barr virus (EBV)-DNA in cerebrospinal fluid (CSF) in detecting HIV-positive primary CNS lymphoma (PCNSL) has been established, its usefulness for identifying CNS involvement of systemic ARL remains elusive. In this study, we evaluated the utility of the EBV-DNA load in CSF in identifying CNS involvement in patients with systemic ARL. Methods We retrospectively reviewed the clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In the cART era, the frequency of HIV-associated PCNSL has fallen whilst survival has improved [91], although outcomes remain inferior to those of immunocompetent patients [92]. Surrogate measures are often used for diagnosis, using a combination of thallium-201 SPECT scanning and presence of EBV in the CSF [93, 94], therefore availability of diagnostic material for biologic studies is limited. With increasing use of intensive treatment regimens, however, histological diagnosis will have a greater influence on choice of treatment and should be obtained where feasible.…”
Section: Treatmentmentioning
confidence: 99%
“…In the cART era, the frequency of HIV-associated PCNSL has fallen whilst survival has improved [91], although outcomes remain inferior to those of immunocompetent patients [92]. Surrogate measures are often used for diagnosis, using a combination of thallium-201 SPECT scanning and presence of EBV in the CSF [93, 94], therefore availability of diagnostic material for biologic studies is limited. With increasing use of intensive treatment regimens, however, histological diagnosis will have a greater influence on choice of treatment and should be obtained where feasible.…”
Section: Treatmentmentioning
confidence: 99%
“…A diagnosis of EBV encephalitis may be considered when viral DNA is detected in the CSF, but the clinical significance of this finding is often unclear. EBV can be a bystander in the presence of other infections and even non‐infectious demyelinating or degenerative diseases . Approximately 15–25% of immunocompromised patients with a CNS opportunistic infection will also have a positive EBV PCR , albeit often with low viral load .…”
Section: Discussionmentioning
confidence: 99%
“…EBV can be a bystander in the presence of other infections and even non‐infectious demyelinating or degenerative diseases . Approximately 15–25% of immunocompromised patients with a CNS opportunistic infection will also have a positive EBV PCR , albeit often with low viral load . It has been suggested that sensitive EBV assays may detect latent virus carried in B cells in the CSF .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plasma controllers (HIV RNA <20 copies/mL, n=97) CSF EBV DNA was detectable in 13 160 individuals (13.4%): it was associated with pleocytosis (50% vs. 8.4%, p=0.001), higher CSF HIV 161 RNA in those with detectable viral load (2.28 vs. 1.85 Log 10 copies/mL, p=0.011) and higher CSF 162 neopterin levels [2.81 ng/mL vs. 0.77 ng/mL, p=0.012] (Figure 3). In CSF controllers (CSF HIV RNA 163 <20 copies/mL, n=84) CSF EBV DNA was detectable in 10 individuals (11.9%): it was associated with 164 pleocytosis (66.6% vs. 6.9%, p<0.001) and border-line higher CSF neopterin (3. Several studies reported the role of EBV in immunocompromised patients and they showed that the 174 detection of EBV DNA in the CSF is a good marker of primary central nervous system lymphoma 175 (PCNSL, with sensitivity and specificity of 70% and 80%) [19] [20] [21] [22]. Some studies reported 176 the development of PCNSL in HIV-infected EBV-positive patients [23] [24] [25] [26].…”
Section: Introduction 70mentioning
confidence: 99%